Anatomi Organ Hati dan Fungsinya dalam Metabolisme - Novrina Situmorang (Universitas Methodist Indonesia, 2026)
The liver is a vital organ that plays a crucial role in various physiological processes in the body, particularly metabolism. This article discusses the anatomy of the liver, which consists of four main lobes and a functional unit called the hepatic lobule. It also discusses its role in carbohydrate, fat, and protein metabolism, detoxification, and bile production. The liver maintains blood glucose balance through glycogenesis, glycogenolysis, and gluconeogenesis. It also produces lipoproteins, cholesterol, and plasma proteins, and neutralizes toxic substances through detoxification. With these functions, the liver is a crucial control center for the body's metabolism. Efforts to maintain liver health are necessary to support optimal liver function